A Cell-free Biodegradable Synthetic Artificial Ligament for the Reconstruction of Anterior Cruciate Ligament in a Rat Model. (February 2021) - Kawakami, Yohei; Nonaka, Kazuhiro; Fukase, Naomasa; Amore, Antonio D'; Murata, Yoichi; Quinn, Patrick; Luketich, Samuel; Takayama, Koji; Patel, Kunj G.; Matsumoto, Tomoyuki; Cummins, James H.; Kurosaka, Masahiro; et al.
Graphical abstract: Image, graphical abstract ABSTRACT: Traditional Anterior Cruciate Ligament (ACL) reconstruction is commonly performed using an allograft or autograft and possesses limitations such as donor site morbidity, decreased range of motion, and potential infection. However, a biodegradable synthetic graft could greatly assist in the prevention of such restrictions after ACL reconstruction. In this study, artificial grafts were generated using "wet" and "dry" electrospinning processes with a biodegradable elastomer, poly (ester urethane) urea (PEUU), and were evaluated in vitro and in vivo in a rat model. Four groups were established: (1) Wet PEUU artificial ligament, (2) Dry PEUU artificial ligament, (3) Dry polycaprolactone artificial ligament (PCL), and (4) autologous flexor digitorum longus tendon graft. Eight weeks after surgery, the in vivo tensile strength of wet PEUU ligaments had significantly increased compared to the other synthetic ligaments. These results aligned with increased infiltration of host cells and decreased inflammation within the wet PEUU grafts. In contrast, very little cellular infiltration was observed in PCL and dry PEUU grafts. Micro-computed tomography analysis performed at 4 and 8 weeks postoperatively revealed significantly smaller bone tunnels in the tendon autograft and wet PEUU groups. The Wet PEUU grafts served as an adequate functioning material and allowed for the creation of tissues that closely resembled the ACL.